Implementasi Profil Pelajar Pancasila Melalui Problem Based Learning pada Pembelajaran Pemupukan di SMK Negeri 1 Bawen - Dzulqoh, Fina Muftihah; Nurwahyuningsih, Atip; Maulida, Zanny Varah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study aims to analyze the implementation of Pancasila Student Profile through Problem-Based Learning (PBL) model on fertilization material at SMK Negeri 1 Bawen. The PBL model is used to provide active learning experiences to students by presenting real problems as a starting point for learning. Through a descriptive qualitative approach, this research reveals how the six dimensions of the Pancasila Student Profile - faith and piety in God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity - are integrated in the steps of PBL, from problem orientation to process evaluation. The results showed that PBL was effective in shaping students' character according to Pancasila values while improving students' understanding of fertilization material. This study recommends the application of PBL in other subjects to support the strengthening of student character.